'Word of God' and 'Spirit of God' in Christian and Islamic christologies a starting point for interreligious dialogue? - Jørgensen, Jonas Adelin 1973- (2009)
The article discusses whether the seemingly similar notions of Jesus as ‘word’ of God and the role of the spirit in relations between Jesus and God might serve as a starting point for dialogue and deeper appreciation between Christianity and Islam. The article briefly reviews the biblical and qur'anic material on these concepts as they have been interpreted in Christian and Islamic theological traditions. This brief review is needed in order to present the Christological reflection among a group of so-called Īsā imandars, a syncretistic Christian–Islamic group in Bangladesh, and to evaluate their claim that there is a similarity between Christian and Islamic concepts. The presentation focuses on how they interpret Jesus as ‘Word of God’ and ‘Spirit of God’ in the borderland between Islam and Christianity. In conclusion, the article discusses how the clear systematic-theological incompatibility and the simultaneous lived compatibility of Christological titles and descriptions should be evaluated in answering the initial question of whether or not common concepts are helpful for dialogue and understanding between Christianity and Islam.
Keywords: Dialog; Christentum; Islam; Christologie; Dialogue; Christianity; Christology